Case Report: Pathological complete response yet early brain relapse in HER2-positive breast cancer: a case-based review - Feng, Jing; Tong, Yujun; Zhang, Zhen; He, Yuanli (Frontiers in Immunology, 2026)
Despite advances in anti-HER2 therapies leading to high pathological complete response (pCR) rates, the blood-brain barrier (BBB) still shelters micrometastatic deposits, so intracranial relapse continues to pose a formidable therapeutic obstacle in HER2-positive breast cancer (BC). Understanding the mechanisms underlying early central nervous system (CNS) relapse and integrating BBB-penetrant strategies remain urgent unmet needs. We report a 60-year-old woman with HER2-positive, hormone receptor-negative breast cancer who achieved pCR after neoadjuvant docetaxel combined with trastuzumab and pertuzumab, followed by 12 months of maintenance trastuzumab and pertuzumab. Despite achieving pCR and comprehensive systemic control, the patient developed multifocal brain metastases two months after completing maintenance therapy, without extracranial recurrence. This case underscores the limitations of large-molecule monoclonal antibodies in preventing CNS recurrence due to poor BBB permeability, allowing dormant CNS-adapted clones to persist and later expand. Emerging CNS-active therapies, including small-molecule tyrosine kinase inhibitors (TKIs) such as tucatinib and next-generation antibody-drug conjugates (ADCs) like trastuzumab deruxtecan, have shown promising intracranial activity. In addition, advanced strategies such as intensified MRI surveillance, radiomics, liquid biopsy, focused ultrasound-mediated BBB disruption, nanoparticle delivery systems, and radionuclide therapy offer potential avenues for early identification and prevention of cerebral metastases.